LITERATURE REVIEW: TELENURSING AND THE ADHERENCE OF HEMODIALYSIS PATIENTS - Wulandari; Peristiowati, Yuly; Ellina, Agusta Dian; Fajriah, Asruria Sani (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
Background: A health problem in hemodialysis patients is non-compliance with fluid restrictions. The country with the highest incidence of end-stage renal disease in 2018 was the Jalisco region in Mexico, with 594 people per million. One of the efforts to improve patient compliance is through education and monitoring. Telenursing is one of the modern information and communication technology systems in the health sector that can be used for patient monitoring and providing nursing services. Purpose: To determine telenursing's effect on dialysis patients' adherence. Methods: The research articles were obtained from three databases, ProQuest, PubMed, and Google Scholar, with 27 articles. Search literature using keywords (Bahasa and English), telenursing OR text messaging OR telephone Follow-up OR short message system OR mobile phone text messaging AND adherence OR Compliance AND hemodialysis OR dialysis with the inclusion criteria of research articles from 2016-2020, primary articles, full text, and research subjects were hemodialysis patients (either primary or secondary). The seven articles obtained were critically assessed and analyzed using Duffy's Research Appraisal Checklist Approach. Results: Telenursing research showed increased adherence in the presence of hemodialysis, fluid restriction, medicine, dietary, physical activity, and intention to quit smoking also increased knowledge, quality of life, and self-efficacy of a dialysis patient. Conclusion: Telenursing increases adherence to care and treatment of dialysis patients and improves health status in chronic diseases.